Fenomena Gaya Konsumsi Gen Z di Kota Malang Terhadap Fast Fashion Dalam Perspektif Globalisasi Budaya - Nur Anisa Fadila Umar; Wafa; Lady Aqilla Balerina; Grace Octavia Ilanunu; Nur Ma'rifatul Amalia (Jurnal Riset Multidisiplin Edukasi, 2025)
The intensification of cultural globalization through digital media has significantly transformed the ways Generation Z interprets consumption, particularly in fast fashion practices. This phenomenon extends beyond the fulfillment of basic clothing needs and has become a site for the construction of social identity and symbolic meaning within the global cultural sphere. This study aims to examine the consumption patterns of Generation Z in Malang City toward fast fashion from the perspective of cultural globalization, focusing on the factors shaping consumption behavior and the dynamics of global–local value negotiation. This research employs a descriptive qualitative approach within an interpretive paradigm through a literature study. The data consist of secondary sources obtained from academic journals, scholarly articles, and relevant books, which are analyzed using thematic analysis as developed by Braun and Clarke. The analytical process involves coding, theme development, and interpretive analysis linked to theories of symbolic consumption, cultural globalization, McDonaldization, and fast fashion. The findings indicate that Generation Z’s fast fashion consumption is predominantly symbolic, with fashion products serving as representations of identity, social legitimacy, and self-expression. Social media and influencers emerge as dominant external factors driving impulsive consumption through the mechanism of Fear of Missing Out, while internal factors such as identity exploration and hedonistic orientation further reinforce consumptive behavior. Moreover, the study reveals an ongoing negotiation between global and local values in fashion consumption practices, although sustainability awareness has not yet been fully translated into actual consumer behavior. This study concludes that the fast fashion consumption patterns of Generation Z in Malang City result from a complex interaction between global cultural influences, digital dynamics, and local social contexts.